2019
DOI: 10.1101/2019.12.20.885590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low basal expression and slow induction of IFITM3 puts immune cells at risk of influenza A infection

Abstract: The interferon-induced transmembrane protein, IFITM3, has been shown to restrict influenza virus infection in murine and in vitro settings for ten years, but no explanation has been found to explain why this virus infection is so highly contagious and infects most individuals it comes in contact with. We confirm that the expression level of IFITM3 plays a role in determining the level of viral infection through manipulation of IFITM3 levels with interferon (IFN) stimulation and overexpression systems. Low basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Downregulation of the IFN-stimulated gene was still pertained despite increased JAK-STAT signaling in the WTAGAAAYY epitope-binding T EM1 cells in the severe group compared to mild COVID-19. As previously described, IFITM proteins have been implicated in the restriction of SARS-CoV-1 cellular entry 43 and baseline expression of IFITM3 has been shown to determine the susceptibility to influenza A virus infection 41,42 . It is therefore possible that in individuals who develop only mild COVID-19, a higher baseline expression of IFITM3 restricts cellular entry into CD8 + T cells, therefore leading to reduced viral loads and less impairment of JAK-STAT signaling compared to severely infected patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Downregulation of the IFN-stimulated gene was still pertained despite increased JAK-STAT signaling in the WTAGAAAYY epitope-binding T EM1 cells in the severe group compared to mild COVID-19. As previously described, IFITM proteins have been implicated in the restriction of SARS-CoV-1 cellular entry 43 and baseline expression of IFITM3 has been shown to determine the susceptibility to influenza A virus infection 41,42 . It is therefore possible that in individuals who develop only mild COVID-19, a higher baseline expression of IFITM3 restricts cellular entry into CD8 + T cells, therefore leading to reduced viral loads and less impairment of JAK-STAT signaling compared to severely infected patients.…”
Section: Discussionmentioning
confidence: 89%
“…3C). IFITM3 has previously been reported to confer protection against H1N1 influenza A virus 41,42 and IFITM proteins have been shown to restrict cellular entry of SARS-CoV-1 43 . Therefore, our finding could indicate a potential role for IFITM3 in protection from severe courses of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that IFN-λ is secreted by Plasmacytoid dendritic cells (pDC) that respond to this cytokine in an autocrine manner to surge the anti-viral responses (29). Moreover, Wellington et al (30) have found that IFN-λ induce IFITM3 expression in pDC cells to a level similar to induction by type I IFN. IFITM3 produces an immune effector protein that promotes mucosal immune cell durability by increasing CD8+CTL number in the airways, which is vital in immunity against viral diseases.…”
Section: Discussionmentioning
confidence: 99%